2008
DOI: 10.3347/kjp.2008.46.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Sequence Tags of Trichinella spiralis Muscle Stage Larvae

Abstract: Abstract:In order to obtain greater insight into the relevant genomic expression patterns of Trichinella spiralis, 992 expressed sequence tags (ESTs) were collected from a cDNA library of T. spiralis muscle stage larvae and assembled into 60 clusters and 385 singletons. Of them, 445 (44.7%) ESTs were annotated to their homologous genes, and small fractions were matched to known genes of nematodes. The annotated ESTs were classified into 25 eukaryotic orthologous groups (KOG). Cytochrome C oxidase (34 clones) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…[ 26 ] and Park et al . [ 27 ]) revealed 73, 57 and 0 ESTs of this gene in the ML (5 020 ESTs), Ad (2 981 ESTs) and NBL (3 234 ESTs) databases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] and Park et al . [ 27 ]) revealed 73, 57 and 0 ESTs of this gene in the ML (5 020 ESTs), Ad (2 981 ESTs) and NBL (3 234 ESTs) databases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Kouzaki et al [ 29 ] reported that proteases induce production of TSLP through PAR2, and TSLP triggers dendritic cell-mediated Th2 type inflammation. Trichinella also excreted and/or secreted various kinds of proteases for invasion and digestion of host tissues [ 11 - 13 ], and these proteases might elicit TSLP via PAR2.…”
Section: Discussionmentioning
confidence: 99%
“…T. spiralis larvae have been shown to be able to establish chronic infections in the skeletal muscles of immunocompetent hosts [ 10 ]. They also expressed a greater variety of proteases, particularly serine protease and aspartic protease, in larval stages as compared to the adult worm stage, and these proteases might be necessary to infect new hosts [ 11 - 13 ]. T. spiralis could evoke a host Th2 immune response, and the host also elevates its Th2 immune responses in order to eliminate the worms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%